Characterization of the Phenotypic and Genotypic Antibiotic Resistance Markers in Escherichia coli (E. coli) Associated With Diabetes and Nondiabetic Patients - David Nana Adjei; Thomas Stuart Mughogho; Olu-Taiwo Michael; Sarah Saidu; Gloria Amegatcher; Akua Obeng Forson (International Journal of Microbiology)
Conclusion: We observed blaCTX-M as the most common ESBL genotype, in combination with other ESBL genes present in some E. coli isolates. Nitrofurantoin and ceftriaxone antibiotics were efficacious. Appropriate prescription of antibiotic therapy, and the prevention of transmission of resistant genes in the context of public health can be facilitated by routine monitoring of the resistance profiles and ESBL markers in patients with and without diabetes.